An Animal-Source Food Supplement Increases Micronutrient Intakes and Iron Status among Reproductive-Age Women in Rural Vietnam. Issue 6 (19th April 2017) - Hall, Andrew G; Ngu, Tu; Nga, Hoang T; Quyen, Phi N; Hong Anh, Pham T; King, Janet C
Abstract: Background: Few studies have examined the impact of local animal-source foods (ASFs) on the nutritional status of reproductive-age women in developing countries. Objective: We hypothesized that a midmorning snack of local ASF for 6 mo would reduce dietary micronutrient deficiencies [usual intake less than the estimated average requirement (EAR)] and improve blood biomarkers of iron, zinc, and vitamins A and B-12 status among nonpregnant, reproductive-age women in rural Vietnam. Methods: One hundred seventeen women, 18–30 y old, were randomly assigned to receive either an ASF (mean: 144 kcal, 8.9 mg Fe, 2.7 mg Zn, 1050 μg retinoic acid equivalent vitamin A, and 5.5 μg vitamin B-12) or a control snack (mean: 150 kcal, 2.0 mg Fe, 0.9 mg Zn, 0 μg retinoic acid equivalent vitamin A, and 0 μg vitamin B-12) 5 d/wk for 6 mo. Usual nutrient intakes were estimated by repeated 24-h dietary recalls. Blood samples were collected at baseline and 3 and 6 mo. Because of the relation between nutritional status and inflammation, serum C-reactive protein, α-1-acid-glycoprotein, and urinary tract infections (UTIs) were also monitored. Results: Eighty-nine women (47 in the ASF group and 42 controls) completed the study. In the ASF group, intakes of iron and vitamins A and B-12 below the EAR were eliminated, and the prevalence of a low zinc intake was reduced to 9.6% compared with 64.7% in controls ( P < 0.001). At 6 mo, a modest increase ( P < 0.05) in hemoglobin and iron status occurred in the ASF group compared with the control group, but plasma zinc, retinol, and serum vitamin B-12 concentrations did not differ. UTI relative risk was 3.9 ( P < 0.05) among women assigned to the ASF group who had a low whole-body iron status at baseline. Conclusions: Adding a small amount of locally produced ASF to the diets of reproductive-age Vietnamese women improved micronutrient intakes and iron status. However, the increased UTI incidence in women in the ASF group with initially lower iron stores warrants further investigation.